Determination of Necessity of Ureteral Stenting after Uncomplicated Ureteroscopic Lithotripsy for Distal Ureteral Calculi (Journal of Dhaka National Medical College & Hospital, 2024)
Objectives: To determine the necessity of ureteral stenting after uncomplicated ureteroscopic lithotripsy for distal ureteral calculi (≤15mm).Materials & Methods: This prospective comparative study was conducted in the Department of Urology at Dhaka Medical College, Dhaka from July 2016 to June 2018. Study population included the patients aged 18 to 60 years whoattended in the outpatient Department of Urology, Dhaka Medical College Hospital, Dhaka with distal ureteric stone (≤15mm). After admission patients were studied clinically andwas selected for treatment and study purpose as per selection criteria. A total of 60 patients included with distal ureteric stone underwent uncomplicated ureteroscopic lithotripsy using a pneumatic device without ureteral dilatation. They were randomized equally into non-stented Group-A (n=30) and stented Group-B (n=30). All the cases were evaluated by history taken and relevant investigations were done. Each patient was followed up and evaluated at immediate(day 1-3), after 2 weeks (1st visit) and after 90 days (2nd visit) postoperatively. Test statistics were used to analyze the data are Chi-square Test, Student "t" test (unpaired) and Fisher's exact probability test. P